Evaluate the Effectiveness of Oral Dosage with Probiotic Bacteria Lactobacillus rhamnosus GG, Lactobacillus Planetarium and Lactobacillus reuteri on Some Immune Indicators in Rabbits - Rahem E. Alziadi (Journal of Global Pharma Technology, 2018)
This study was designed to evaluate some immune Indicators for rabbits oral dosage with three types of probiotics bacteria culture Lactobacillus rhamnosus GG, Lactobacillus planetarium and Lactobacillus reuteri. Rabbits were divided into four treatments, each subjected as the followings: treatment A, used as a negative control. treatment B,  sub divided into four groups: group1 used as a positive control  and other three groups were oral dosage with 1.0 µl\100gm weight\day with Lactobacillus rhamnosus GG, Lactobacillus planetarium  and Lactobacillus reuteri . Treatments C and D, the dose used was 200and 300µl\100gm weight\day from same. The results showed increasing in white blood cells (WBCs), red blood cells (RBCs) and hemoglobin (HB) and other parameters like immune origins weight (liver and spline) according to type of oral dosage bacteria and amount of dose, the dosage with Lb. rhamnosus GG bacteria was the beast compared with Lactobacillus planetarium  which were better than Lactobacillus reuteri dosage  and control. The study showed that dosage with 300µl\100gm weight\day was best comparing with other treatments and control respectively.Keywords: Oral dosage, Probiotics bacteria, Probiotics dose, Immune Indicators.